Drug-free ASEAN 2025: Tantangan Indonesia dalam Penanggulangan Penyalahgunaan Narkoba - Herindrasti, Valentina Lusia Sinta (Jurnal Hubungan Internasional, 2018)
This article examines Indonesia’s initiatives in combating and preventing drugs abuse which has reached the level of ‘drugs emergency’. Although there are many advantages in this new approach, this article argues that the implementation of the rehabilitation approach still faces various challenges such as policy implementation priority, mindset changing of the executors, un-fully operational system, infrastructure availability, reliable rehabilitation method test, which generate questions on the effectiveness of the decriminalization policy. In the future, continuous evaluation is needed to make sure that the policy is well implemented and provides impact as is expected, which is to decrease the number of drug abusers.